Computational Investigation of the Interaction Between Hydrogen Atoms and an Intense Circularly Polarized Laser Field (Communications in Computational Physics, 2012)
The study of interactions between a high-power laser and atoms has beenone of the fundamental and interesting topics in strong field physics for decades. Basedon a nonperturbative model, ten years ago, we developed a set of programs to facilitatethe study of interactions between a circularly polarized laser and atomic hydrogen.These programs included only contribution from the bound states of the hydrogenatom. However, as the laser intensity increases, contribution from continuum states tothe excitation and ionization processes becomes larger and can no longer be neglected.Furthermore, because the original code is not able to add this contribution directlydue to its many disadvantages, a major upgrade of the code is required before including the contribution from continuum states in future. In this paper, first we deducesome important formulas for contribution of continuum states and present modifications and tests for the upgraded code in detail. Second we show some comparisonsamong new results, old results from the original codes and the available experimentaldata. Overall the new result agrees with experimental data well. Last we present ourcalculation of above-threshold ionization (ATI) rate and compare it with a pertubative calculation. The comparison shows that our nonperturbative calculation can alsoproduce ATI peak suppression.